Artefact collecting: creating or destroying the archaeological record? - Barford, Paul M. (Folia Praehistorica Posnaniensia, 2020)
This paper examines some of the arguments used by archaeologists in favour of collaborating useful for archaeological research and is a form of public engagement with archaeology. It takes as a case study records of 48 600 medieval artefacts removed from archaeological contexts by artefact hunters and recorded by the Portable Antiquities Scheme in England and Wales. The past and potential uses of these records as an archaeological source are objectively reviewed, together with an assessment of the degree to which they provide mitigation of the damage caused to the otherwise unthreatened archaeological record. It is concluded that, although information can be obtained by studying records of findspots of addressed artefacts such as coins, in general the claims made in support of professional archaeological collaboration with this kind of activity prove to be false.